Different subtypes of nonthyroidal illness syndrome on the prognosis of septic patients: a two-centered retrospective cohort study - Ning, Ning; Li, Juan; Sun, Wenwu; Ma, Chaoping; Li, Jiaoyan; Sheng, Huiqiu; Chen, Ying; Zhao, Bing; Zhang, Jiyuan; Zhu, Jiyue; Gao, Chengjin; Mao, Enqiang (Frontiers in Endocrinology, 2023)
Background Nonthyroidal illness syndrome (NTIS) is a common endocrine dysfunction predicting unfavorable outcomes in critical illness. The objective of the study is to evaluate the association between different NTIS subtypes with outcomes in septic patients. Methods Septic patients in two Chinese academic centers from October 2012 and October 2022 are enrolled in analysis. Multivariable regressions are used to assess associations between NTIS and outcomes. Outcomes include in-hospital mortality, length of stay in hospital (LOS), non-invasive ventilation failure and weaning failure. Patients with NTIS are categorized into 4 types according to the different levels of FT4 and TSH. The association between different NTIS subtypes and mortality are further analyzed. Survival curve is plotted using the Kaplan-Meier method.Results After screening, a total of 1226 septic patients with complete thyroid hormones result are eventually enrolled. Among them, 520 (42.4%) patients are diagnosed as NTIS. In multivariable regression analysis, NTIS is independently associated with increased 30-days mortality (OR=1.759, CI 1.009-3.104, p=0.047), but has no association with 60-days mortality (OR=1.524, CI 0.893-2.618, p=0.123), 90-days mortality (OR=1.411, CI 0.831-2.408, p=0.203), LOS, non-invasive ventilation failure or weaning failure. In NTIS subtypes, NTIS patients with low FT3 and TSH levels, regardless of the FT4 values, have significantly higher mortality than euthyroid patients OR= 6.488, p=0.01; OR=3.973, p=0.046; OR=3.849, p=0.051). This result is consistent in patients with low FT3 and FT4 levels, regardless of the TSH values OR=3.349, p=0.006; OR= 2.594, p=0.024; OR=2.55, p=0.025). There is no survival difference between NTIS patients with low FT3 only and euthyroid patients. Survival plot shows the worst prognosis is in NTIS patients with low FT3, FT4 and TSH level.Conclusions NTIS is frequent in sepsis. A reduction of FT3 together with FT4 or TSH, but not FT3 only, is associated with an increased risk of mortality.